2014
DOI: 10.1016/j.cmet.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The LYR Factors SDHAF1 and SDHAF3 Mediate Maturation of the Iron-Sulfur Subunit of Succinate Dehydrogenase

Abstract: Summary Disorders arising from impaired assembly of succinate dehydrogenase (SDH) result in a myriad of pathologies, consistent with its unique role in linking the citric acid cycle and electron transport chain. In spite of this critical function, however, only a few factors are known to be required for SDH assembly and function. We show here that two factors, Sdh6 (SDHAF1) and Sdh7 (SDHAF3), mediate maturation of the FeS cluster SDH subunit (Sdh2/SDHB). Yeast and Drosophila lacking SDHAF3 are impaired in SDH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 37 publications
4
110
1
Order By: Relevance
“…These include ISD11, the obligate NFS1-binding partner [107], SDHAF1 and SDHAF3, the latter two of which were recently shown to be involved in mediating the maturation of the SDHB [108]. Additionally, Winge"s group has also shown that the LYRM protein, Mzm1, functions in the insertion and/or stabilization of the ISC-containing subunit of complex III [109].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These include ISD11, the obligate NFS1-binding partner [107], SDHAF1 and SDHAF3, the latter two of which were recently shown to be involved in mediating the maturation of the SDHB [108]. Additionally, Winge"s group has also shown that the LYRM protein, Mzm1, functions in the insertion and/or stabilization of the ISC-containing subunit of complex III [109].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, SDHAF1 interacts with the C-terminus of SDHB, raising the possibility that it participates in biogenesis of the SDH complex by providing nascent Fe-S clusters to SDHB (Maio et al, 2014). Previous studies in S. cerevisiae concluded that Sdh6, the SDHAF1 ortholog, exerts its function on SDH assembly by binding to and protecting an Sdh1-Sdh2 intermediate (SDHA-SDHB in human, respectively) from the deleterious effects of oxidants (Na et al, 2014). However, the human protein failed to rescue the respiratory defect of a Δ Sdh6 yeast strain (Ghezzi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…SDHAF2, an assembly protein that flavinates SDH, is also implicated in paragangliomas. Recently, two additional Fe-S assembly proteins, SDHAF1 and SDHAF3, were found to stabilize Fe-S cluster assembly in SDH 190 . The later two proteins have LYR-motifs (Leu-Tyr-Arg) common to proteins involved in Fe-S cluster assembly.…”
Section: Fe-s Clustersmentioning
confidence: 99%